Japanese funeral at the Buddhist Church of San Jose - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of a Japanese funeral, held at the San Jose Buddhist Church Betsuin located at 640 North Fifth Street in the Japantown section of Central San Jose